Sztuka ludowa Polski Ludowej w refleksji etnologicznej - Sadowska, Joanna (Zeszyty Wiejskie, 2010)
Folk art is one of the key research areasof ethnology, since it has been fully constituted as an independent academic discipline. It occupied a special place in ethnological studies in the times of Polish People's Republic. This article is an attempt to show the specific approach to folk art in this period. It provides adescription of different methodological positions of individual researchers involved in this issue and the differences in approach to the patron age of folk art and its creators.